Дослідження еволюції залишкових знань у великих навчальних системах - Yasinsky, V. V.; Boldak, A. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
On the basis of generalization of the results of intellectual data analysis of end-of-term complex quality monitoring of the specialists training quality in NTUU "KPI" and monitoring of the preliminary training participants knowledge quality, the phenomenon of self-organization of residual education knowledge as a complex, non-linear, dynamic process is discovered and investigated. Its regularities for the short-term and long-term residual knowledge are identified, the sequence of the stages of these knowledge structure formation is set.